PSYCHOSOCIAL FACTORS DETERMINING PROGNOSIS IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - N. B. Lebedeva; O. L. Barbarash (Российский кардиологический журнал, 2003)
Psychosocial factors determining prognosis in patients with acute myocardial infarction.